BEING BORN ...IS IT A NATURAL OR ON ARTIFICIAL PROCESS? - Maria de Lourdes Centa (Universidade Federal do Paraná, 1996)
A literature review about the paradox of a simple/complex phenomenon of being born/ not being in which the author reflects about its importance theroughout the ages. The author also at tempts to clarify knowledge about the fenomenon of study by searching in the philosophy answers to the issue of being borns as a natural or on artificial process.